A Selection of Constitutional Perspectives on Human Kidney Sales - Venter, Bonnie (Potchefstroom Electronic Law Journal, 2017)
There are thousands of desperate people globally who need a kidney for transplantation. The number of people who require a kidney transplant continues to escalate faster than the number of kidneys available for a transplant. The specific focus of this article is to determine whether the payment of kidney donors could be regarded as constitutionally acceptable or not. To establish the constitutional acceptability of the reimbursement of kidney donors the following rights are analysed: the right to life, the right to human dignity, the right to self-determination, the right to privacy, and the right of access to healthcare services. Case law regarding the above is also included. After careful consideration of all of the above it is concluded that it should be regarded as constitutionally acceptable to remunerate a kidney donor for his kidney.